Mining Data From Plasma Cell Differentiation Identified Novel Genes for Engineering of a Yeast Antibody Factory - Koskela, Essi V.; Gonzalez Salcedo, Alina; Piirainen, Mari A.; Iivonen, Heidi A.; Salminen, Heidi; Frey, Alexander D. (Frontiers in Bioengineering and Biotechnology, 2020)
Saccharomyces cerevisiae is a common platform for production of therapeutic proteins, but it is not intrinsically suited for the manufacturing of antibodies. Antibodies are naturally produced by plasma cells and studies conducted on plasma cell differentiation provide a comprehensive blueprint for the cellular transformations needed to create an antibody factory. In this study we mined transcriptomics data from plasma cell differentiation to improve antibody production by S. cerevisiae. Through data exploration, we identified several new target genes. We tested the effects of 14 genetic modifications belonging to different cellular processes on protein production. Four of the tested genes resulted in improved antibody expression. The ER stress sensor IRE1 increased the final titer by 1.8-fold and smaller effects were observed with PSA1, GOT1 and HUT1 increasing antibody titers by 1.6-, 1.4- and 1.4-fold. When testing combinations of these genes, the highest increases were observed when co-expressing IRE1 with PSA1, or IRE1 with PSA1 and HUT1, resulting in 3.8-fold and 3.1-fold higher antibody titers. In contrast, strains expressing IRE1 alone or in combination with the other genes produced similar or lower levels of recombinantly expressed yeast acid phosphatase compared to the controls. Using a genetic UPR responsive GFP reporter construct, we show that IRE1 acts through constitutive activation of the unfolded protein response. Moreover, the positive effect of IRE1 expression was transferable to other antibody molecules. We demonstrate how data exploration from an evolutionary distant, but highly specialized cell type can pinpoint new genetic targets and provide a novel concept for rationalized cell engineering.